Determinants of the non-technical losses in Sarawak's electricity provider - Feroz, Hayat Khan (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Electricity has become a necessity to the entire human race since its discovery in the 18th century whereby its utilization had evolved tremendously from the creation of a mere battery to light up bulbs to the massive worldwide generation of electrical power to support and complement people's lives. The electricity supply industry in Malaysia is integrated within a monopolistic nature, whereby a utility company owns and manages the entire generation, transmission, and distribution of electricity in a particular regioy For the state of Sarawa~, Sarawak Energy Berhad (SEB) is the holding company that is principally involved in the power and electricity sector for the Sarawak region with its group of companies under the Sarawak Energy Berhad Group being responsible for the aforesaid three components of electricity Generation, Transmission and Distribution of electricity -in the entire state of Sarawak.